An unusual anomaly of deep venous system in the lower limb: Complete unilateral agenesis of iliofemoral veins in the absence of persistent sciatic vein (Indian Journal of Case Reports, 2019)
Venous anomalies are the most common congenital vascular anomalies. The rarest of these is complete deep venous agenesis. Here, we report a case of a 15-year-old male patient evaluated on color Doppler and computed tomographic venogram with complete right iliofemoral deep venous agenesis with the inferior vena cava continuing as the left common iliac vein and the right popliteal vein draining into superficial anomalous veins of the thigh. These superficial veins were seen to drain through a superficial suprapubic arcuate connector vein into the dilated left common femoral vein. Uniquely in our case, there was no persistent embryonic sciatic vein and no demonstrable reflux into the superficial connector vein, suggesting an uncommon embryological mechanism underlying its pathogenesis. Surgical resection of the dilated superficial veins is absolutely contraindicated in cases of deep venous agenesis and hence accurate diagnosis by the radiologist is absolutely essential in such cases.